2019
DOI: 10.1002/ente.201900136
|View full text |Cite
|
Sign up to set email alerts
|

Toward Data‐Driven Applications in Lithium‐Ion Battery Cell Manufacturing

Abstract: Production chain of lithium‐ion battery cells is a highly complicated system with manifold process–product interdependencies and high sensitivity to ambient conditions. This complexity makes it harder to control and regulate economic and environmental target criteria (e.g., product quality, cost, and energy demand). Therefore, it is necessary to develop a holistic system understanding and to identify and evaluate the interactions between the process steps within the production chain of battery cells and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 31 publications
0
85
0
1
Order By: Relevance
“…Some prospective papers discuss the potential of ML methods to help boosting the discovery of efficient solid electrolyte interfaces. [30,31] The latter focuses on the macroscale. [30,31] The latter focuses on the macroscale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some prospective papers discuss the potential of ML methods to help boosting the discovery of efficient solid electrolyte interfaces. [30,31] The latter focuses on the macroscale. [30,31] The latter focuses on the macroscale.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Few recent works reported automatic ways to collect, store and analyse experimental data in order to allow a better control of the battery production chain thanks to ML methods such as decision tree or random forest. [30,31] The latter focuses on the macroscale. Therefore, the development and application of ML tools able to predict the correlations between the manufacturing parameters and the final properties of LIB electrodes remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] However, their performance, durability, recyclability and CO2 fingerprint require further improvement to make feasible this transition. This can be achieved thanks to materials design, [6][7][8] innovative manufacturing [9][10][11] and manufacturing optimization, [12][13][14] or most likely, thanks to a combination of all of them. Regarding the latter, both experimental and modelling approaches can be used to carry out its optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The blooming Artificial Intelligence (AI) field promises to accelerate the manufacturing optimization by revealing patterns hardly recognizable by "classical" analysis methods. 14,[32][33][34][35][36][37] As they do not rely on physical models, the feasibility of this approach depends on the capability to generate high quality datasets (from experiments, physical models or both of them simultaneously) complete enough to describe the battery manufacturing, which most likely represents the limiting step to develop AI models. Takagishi et al recently reported a machine learning (ML) approach in which the datasets were built by randomly generating in silico electrode mesostructures composed of only AM particles coupled with a zerodimensional electrochemical model to calculate the charge/discharge specific resistance.…”
Section: Introductionmentioning
confidence: 99%